2018
DOI: 10.1002/cplu.201800097
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical Characterisation on Surface‐Inverted Black Silicon Photocathodes by Using Platinum/Palladium Co‐catalysts for Solar‐to‐Hydrogen Conversion

Abstract: Black silicon (bSi) has recently captured research attention in photoelectrochemical (PEC) solar‐to‐hydrogen (STH) conversion devices. Because nanostructuring of silicon retains the photovoltaic attributes of the material, it also provides a range of excellent physicochemical properties, such as a vast active‐site‐rich electrochemical interface, owing to a high aspect ratio, and important light‐scattering attributes, which significantly improve photoconversion. One method to gain control over p‐type bSi interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
(177 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, the metal surface may pro vide active sites to lower the kinetic barrier for redox reac tions. Typical examples can be found in photoelectrochemical systems for H 2 production [11,12] and CO 2 reduction [13,14]. In addition to improving charge separation, metals such as Au, Ag and Cu have peculiar surface plasmon resonance (SPR) absorption that can promote solar spectrum harvesting to enhance the photoconversion efficiency as well [15].…”
Section: Metal-semiconductor Heterostructuresmentioning
confidence: 99%
“…On the other hand, the metal surface may pro vide active sites to lower the kinetic barrier for redox reac tions. Typical examples can be found in photoelectrochemical systems for H 2 production [11,12] and CO 2 reduction [13,14]. In addition to improving charge separation, metals such as Au, Ag and Cu have peculiar surface plasmon resonance (SPR) absorption that can promote solar spectrum harvesting to enhance the photoconversion efficiency as well [15].…”
Section: Metal-semiconductor Heterostructuresmentioning
confidence: 99%
“…The photoelectrochemical (PEC) biosensor, as a newly popular sensing technique, has been recognized as an elegant method for sensing trace analytes. In a PEC sensing platform, the photoinduced current is employed as the detection signal, which plays a decisive role in highly sensitive detection. Currently, the deposition of noble metal nanoparticles on the surface of semiconductors has been widely used in many PEC sensing systems due to the significant enhancement in photocurrent by their intrinsic plasmonic effect. Moreover, when the contact between metal and semiconductor happens, a distinct Schottky junction can be established to promote the transfer and separation of the photogenerated electrons. Note that the ultimate small size limit of the metal nanoparticle is a single atom, which can be stabilized by the neighboring surface atoms on the support. , Using single atoms as alternatives to nanoparticles, such nanostructured photoactive materials not only reduce the noble metal dosage but also display distinct properties. The single-atom-based photoactive material can fully inherit the fast charge carrier separation ability in a metal nanoparticle–semiconductor junction. , On the other hand, the introduction of single atoms into the framework of the semiconductors can effectively modulate the energy band and electronic structures to improve their corresponding light-harvesting and charge transport behaviors. Meanwhile, the interfacial redox reactions can also be remarkably accelerated by single atoms due to the high catalytic activities of their unique coordination configurations. , The promoted interfacial redox reactions can reduce the aggregation of charge carriers and depress the corresponding recombination at the interface between the semiconductor and electrolyte, which will greatly enhance the PEC performance, as well.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Si photoelectrodes with various micro/nanomorphologies and noble metal catalyst decoration have been widely investigated to enhance the light-capturing capacity and accelerate the kinetics of hydrogen or oxygen evolution reaction (HER or OER) [16][17][18][19]. For instance, Oh et al [16] fabricated a disordered silicon nanowire array (SiNWA) photocathode using the metal-catalyzed chemical etching method and observed that the onset potential was positively shifted by 0.22 V after modification with the Pt catalyst by an electroless deposition process.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Oh et al [16] fabricated a disordered silicon nanowire array (SiNWA) photocathode using the metal-catalyzed chemical etching method and observed that the onset potential was positively shifted by 0.22 V after modification with the Pt catalyst by an electroless deposition process. Halima et al [17] prepared a black Si photocathode covered with an n + -emitter inversion layer and verified that the onset potential could be improved from 0 to 0.26 V RHE after modification with electrodeposited Pd nanoparticles (NPs). Although the noble metal decoration can substantially improve the onset potential, the photocurrent, especially for the planar photoelectrodes, is also reduced due to the increased optical reflection and/or parasitic absorption of the metal catalyst.…”
Section: Introductionmentioning
confidence: 99%